Production traits of tushin sheep i. reproductive ability and growth - Ali Rıza Aksoy; Mustafa Saatcı; Musa Özbey; Muharrem Taşkın Dalcı (Eurasian Journal of Veterinary Sciences)
This study has been conducted to describe the reproductive ability and growth traits of Tushin sheep Forty ewes and 32 lambs were used in 1997, and 93 ewes 73 lambs were used in 1998. Rate of birth and rate of twin born were 70.0% and 14,3% in 1997. and 70.0% and 9.8% in 1998 respectively, and the differences between years were not significant. The survival of lambs at 90th day of age were 71.9% and 87.7% (P<0.05) in 1997 and 1998. respectively. The expected mean of birth weight and weaning weight was 3.69±0.01 kg and 17.53±0.08 kg respectively. The age of dam, birth type, sex and year significantly affected the growth traits.